Falls and their association with physical tests, functional capacity, clinical and demographic factors in patients with rheumatoid arthritis - Lourenço, Mariana De Almeida; Roma, Izabela; Assis, Marcos Renato De (Sociedade Brasileira de Reumatologia, 2017)
ABSTRACTObjective: To evaluate the occurrence of falls reported by rheumatoid arthritis patients and its relation to disease activity, functional capacity and physical fitness.Materials and methods: A cross-sectional study constituted by a sample of 97 rheumatoid arthritis patients from the city of Marília (SP) from 2012 to 2013, were assessed for disease activity. Instruments validated for Brazilian population in order to evaluate physical and functional capacity were used. Data analysis was carried out with descriptive statistics, Spearman correlation and Chi-squared test, considering p < 0.05.Results: 88.7% were female subjects with a mean age of 56 (±11.7) years. The median duration of rheumatoid arthritis was 10 years (P25 = 6 and P75 = 17) and the mean of disease activity was 3.6 (±1.3), what was considered a moderate activity. In the last 12 months 37.1% of patients experienced at least one fall, with a total of 52 episodes, and fear of falling was reported by 74.2% of them, but this was not associated to the occurrence of a fall (χ 2 = 1.19, p = 0.27). Gender, number of medications, age, disease activity, duration of rheumatoid arthritis, functional capacity, and physical tests showed no associations with history of falls in the past year.Conclusion: It was observed that the occurrence of falls and the fear of falling are quite common in this population. The occurrence of falls in this sample of rheumatoid arthritis patients bears no relation to disease activity, functional capacity, or physical fitness tests.

RESUMOObjetivo: Avaliar a ocorrência de quedas reportadas por pacientes com artrite reumatoide (AR) e sua associação com a atividade da doença, capacidade funcional e aptidão física.Material e métodos: Estudo transversal com uma amostra de 97 pacientes com AR em Marília (SP), entre 2012 e 2013. Foram usados instrumentos validados na população brasileira para avaliar capacidade física e funcional. Análise dos dados com estatística descritiva, correlações de Spearman e qui-quadrado, considerado p < 0,05.Resultados: Dos pacientes, 88% eram mulheres, média de 56, anos (± 11,7), duração mediana da AR de 10 anos (P25 = 6 e P75 = 17) e média da atividade da doença 3,6 (± 1,3). Nos últimos 12 meses, 37,1% tiveram pelo menos uma queda (total 52 episódios), 74,2% relataram medo de cair, porém sem associação com a ocorrência de quedas (χ2 = 1,19, p = 0,27). Sexo, quantidade de medicamentos, idade, atividade da doença, duração da AR, capacidade funcional e testes físicos não estão associados com história de queda no último ano.Conclusões: Observou-se que a ocorrência de quedas e o medo de cair é frequente nessa população. A ocorrência de quedas nessa amostra de pacientes com AR não está relacionada à atividade da doença, à capacidade funcional e a testes de aptidão física.
Ocorrência de quedas e sua associação com testes físicos, capacidade funcional e aspectos clínicos e demográficos em pacientes com artrite reumatoide
Keywords: Rheumatoid arthritis; Accidental falls; Postural balance; Aptitude tests; Artrite reumatoide; Acidentes por quedas; Equilíbrio postural; Testes de aptidão